Serum Levels of Zinc, Selenium and Homocystine among Iraqi Patients with Type-2 Diabetes Mellitus - Aqeel Abbas Noaman (Journal of Global Pharma Technology, 2016)
Background and Objectives: ( The disease of Diabetes Mellitus ) is a main medical, economic and social big problem, because the high pervasion and increment incidence (of this depilating disease with )subsequent cascading of (several disabling complications) and it needs for special medical care. High prevalence of this disease) occur in Middle East.Its prevalence in Iraq increased from 5% in 1978 to19.7%in 2012). The current study initially focuses on the investigation of serum micronutrients [zinc (Zn), selenium (Se)] and homocystin (Hcy)] levels as well as their relatedness with (type 2 Diabetes Mellitus) in Iraqi patients. Subjects and Methods: This study was designed as a case - control investigation and conducted at diabetic center in Baquba General Hospital in Diayla, Iraq. This study involves 50 patients with type 2 DM and 25 apperently healthy, age and sex matched subjects for that represent as control group. The patients were classified into two sub-groups including, type 2 DM with nephropathy (33 patients) and type 2 DM without nephropathy (17 patients). (Fasting blood sugar, creatinine as well as some selected serum levels including two important micronutrients (Se, Zn) with addition and all of them were measured in each group. Results: The prevalence of DM Type2 was at age of 60 to ≥ 70 years. (Diabetes was more prevalent) in males than in females (58 % , 42 % consecutively) .The mean level of blood glucose and creatinine (were typically higher in both diabetic groups) as compared to the control group (p = .000). Selenium level was lower in diabetic patients with a significant difference when it compared with healthy control. Study groups according to zinc level (p-value= 0.149) did not indicate a significant difference. In this study homocysteine levels was)higher in DM patients with nephropathy than diabetes without nephropathy (17.09±1.942 vs 16.72±2.323) with statistically significant differences comparing with the control group (6.74±0.946) No significant correlation was found among Zn , Se and Hcy with plasma glucose and creatinine. Conclusion: (The findings of the current research show obvious decreased in the serum Se among Type2 DM patients with and without nephropathy comparing with control. Additionally, serum homocystine levels were elevated regarding to the occurrence of diabetic nephropathy so it could be an indicator for observed DM and progression of DM nephropathy.Keywords: Type 2 Diabetes, Zinc, Selenium, Homocysteine.